EFFECTIVENESS OF FAMILY EDUCATION INVOLVEMENT FOR INCREASING STUDENTS INTEREST AND TALENT - Poniman Adyanto (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The results showed: 1) the attitude of the school principal of the family education involvement, administration association, library officers, and parents had a positive attitude towards the effectiveness. 2) the implementation of family education effectively and 3) the parent participation, both participation of ideas, energy, possessions and skills participation is very supportive of the implementation of the family education program in increasing the achievement of students' interests and talents.